2019
DOI: 10.1177/0970846419863872
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Information Sharing, Collaboration and Trust on Vendor–Buyer Relationship

Abstract: This article discovers the vendor–buyer relations in the automotive and constituent industries. More precisely, it examines the cooperative trade associations between all the firms dealing with automobile sector. This article examines the extent of information sharing, trust and collaboration in the commercial networks involved and tries to identify which construct influences the establishment and expansion of channel members’ affiliation. In particular, whether interaction among supply chain members is direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The communication and interaction among students on social media to enhance possibly their relationships with others to expect mutual benefit (Ellison et al , 2007; Hamid et al , 2016). Preliminary studies concluded trust positively affects information sharing by directly writing posts, responding to others’ posts, providing links to sources or uploading a source (Ahmad and Huvila, 2019; Singh et al , 2019; Özer et al , 2011). Hence, the students share information to work together in discussing the concepts and ideas (Su and Chan, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The communication and interaction among students on social media to enhance possibly their relationships with others to expect mutual benefit (Ellison et al , 2007; Hamid et al , 2016). Preliminary studies concluded trust positively affects information sharing by directly writing posts, responding to others’ posts, providing links to sources or uploading a source (Ahmad and Huvila, 2019; Singh et al , 2019; Özer et al , 2011). Hence, the students share information to work together in discussing the concepts and ideas (Su and Chan, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It helps students become acquainted with families, friends and strangers and becomes a potent predictor of sharing activities on SNSs (Kim et al , 2015). Students also use social media as a source of information sharing (Osatuyi, 2013; Singh et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They examine the extent of information sharing, trust, and collaboration in the business networks involved and attempt to determine which structures influence the establishment and expansion of channel member affiliations. In particular, whether the interactions among supply chain members are directly affected by these structures is explored and inferences drawn [8]. The research methodology has a cross-sectional design and is descriptive and exploratory.…”
Section: Related Workmentioning
confidence: 99%